Physical activity and depression among Health and Social Science students at Public Sector University, Dammam, KS - Mubashir Zafar; Yaseen Almabrouk; Mohammed Al Qurain; Jaffer Marzooq (Romanian Journal of Neurology, 2020)
Background. Lack of physical activity and depression are the common problem among university students. The purpose of this study was to compare the physical activity and depression between health science students and social science students at Public Sector University, Dammam, KSA. Methods. It’s a cross sectional study and participant were selected by using multistage cluster sampling. International physical activity questionnaire (IPAQ) and “Becks depression scales were used to determine the physical activity and depression. Students of age group between 20 and 25 years were included. Comparison of depression and physical activity between health and social students was determined through chi square and Man Whitney U test. P value < 0.05 was considered significant. Results. The mean age of participants was 21.09±1.49 years. Among health and social science students, 41.3% and 25.9% were suffering from severe depression respectively (p<0.05). Mean and SD of mild physical activity among health and social science students were 150.96±147.89 and 171.13±160.63 respectively with p value is 0.04. Mean and SD of moderate physical activity among health and social science students were 175.16±157.07 and 204.93±152.57 respectively with p value is 0.06. Mean and SD of vigorous physical activity among students of health and social science were 169.65±148.77 and 219.28±146.04 respectively with p value is 0.05. Conclusion. Results of study found that health science students had high prevalence rate of depression and low level of physical activity compare to social sciences students.